Determination of Heavy Metals Content in Hair in Different Collectives of Albania. - BABI, DIANA; VASJARI, MAJLINDA; LAZO, PRANVERA (Asian Journal of Chemistry, 2010)
The determination of heavy metals, such as mercury, lead, copper, zinc and iron content in hair, for exposed dental workers and unexposed groups of people living in Albania was carried out. The influence of factors such as the age, the sex, the method of daily treatment of hair and the time exposed to mercury, has been in consideration. The mean value of mercury content in hair for the subjects under the study (0.705 μg/g) was found to be lower than the value referred from the World Health Organization (WHO) for the people who do not consume fish with a high methyl mercury content (1-2 μg/g). The content of Hg in different people is found to be different, when exposed and unexposed groups of people were evaluated separately. A significant negative correlation of Fe and Zn was found. The overall mean values of lead, copper, iron and zinc content in hair samples were found to be within the range considered as normal for normal population. Some high' values on iron and zinc content were found for old people. It may not be only the attribution of the age, when oxidizing processes on the organism are more significant, but also of the colour used in hair and relatively high air pollution in Tirana. It was shown, too, that the mean value of iron and zinc in young people (20 to 25 years old) are very close to normal values.